Computational investigation of brownian motion and thermophoresis effect on blood-based casson nanofluid on a non-linearly stretching sheet with ohmic and viscous dissipation effects - Zainal, Nurul Amira; Zuberi, Haris Alam; Lal, Madan; Verma, Shivangi (Tech Science Press, 2024)
Motivated by the widespread applications of nanofluids, a nanofluid model is proposed which focuses on uniform magnetohydrodynamic (MHD) boundary layer flow over a non-linear stretching sheet, incorporating the Casson model for blood-based nanofluid while accounting for viscous and Ohmic dissipation effects under the cases of Constant Surface Temperature (CST) and Prescribed Surface Temperature (PST). The study employs a twophase model for the nanofluid, coupled with thermophoresis and Brownian motion, to analyze the effects of key fluid parameters such as thermophoresis, Brownian motion, slip velocity, Schmidt number, Eckert number, magnetic parameter, and non-linear stretching parameter on the velocity, concentration, and temperature profiles of the nanofluid. The proposed model is novel as it simultaneously considers the impact of thermophoresis and Brownian motion, along with Ohmic and viscous dissipation effects, in both CST and PST scenarios for blood-based Casson nanofluid. The numerical technique built into MATLAB’s bvp4c module is utilized to solve the governing system of coupled differential equations, revealing that the concentration of nanoparticles decreases with increasing thermophoresis and Brownian motion parameters while the temperature of the nanofluid increases. Additionally, a higher Eckert number is found to reduce the nanofluid temperature. A comparative analysis between CST and PST scenarios is also undertaken, which highlights the significant influence of these factors on the fluid’s characteristics. The findings have potential applications in biomedical processes to enhance fluid velocity and heat transfer rates, ultimately improving patient outcomes.